1993
DOI: 10.1002/ijc.2910550421
|View full text |Cite
|
Sign up to set email alerts
|

Importance of mevalonate‐derived products in the control of HMG‐CoA reductase activity and growth of human lung adenocarcinoma cell line a549

Abstract: HMG-CoA reductase catalyzes the synthesis of mevalonate, a crucial intermediate in the biosynthesis of cholesterol and non-sterol isoprenoid compounds essential for cell growth. The HMG-CoA reductase activity of the A549 tumor cell line is higher than that of normal human fibroblasts. This deregulation in mevalonate needs was not due to an alteration in the activated state of the enzyme by short-term regulation. We show that the HMG-CoA reductase in A549 cell line was subject to a multivalent feedback control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 29 publications
3
36
0
4
Order By: Relevance
“…We demonstrated that the expression level of HMG-CoA mRNA in colon cancer tissues is greater than that in the uninvolved mucosa. Similar observations have been reported in leukemia cells (52) and lung cancer cells (53). In addition, our study shows that there is a correlation between HMG-CoA mRNA expression and survivin mRNA expression in colon cancer tissues.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated that the expression level of HMG-CoA mRNA in colon cancer tissues is greater than that in the uninvolved mucosa. Similar observations have been reported in leukemia cells (52) and lung cancer cells (53). In addition, our study shows that there is a correlation between HMG-CoA mRNA expression and survivin mRNA expression in colon cancer tissues.…”
Section: Discussionsupporting
confidence: 92%
“…including prostate cancer and oral cancer [48,49], and dysregulated in lung and breast cancers [50,51]. Our data indicating that MDA-MB-231, that is highly aggressive tumor type representative, has an higher concentration of cholesterol in rafts and resistance to PUFA incorporation are in line to above cited reports.…”
supporting
confidence: 91%
“…[26][27][28][29][30][31] Moreover, large retrospective analyses for drug safety and efficacy trials of statins in coronary artery disease have shown, that not only are these agents able to reduce cardiac disease-related mortality, but cancer incidence is also reduced by 28-33%. 32,33 These data further suggest these agents may have a role in cancer prophylaxis as well as therapy.…”
Section: Figurementioning
confidence: 99%